Stability Enhancement Of Railway Vehicle Dynamics Performance In Lateral Direction Using Fuzzy Bogie-Based Skyhook Control - Harun, Mohamad Hafiz; Zahmani, Qamar Fairuz; Hudha, Khisbullah; Sariman, Mohd Zahar; Harun, Mohd Hanif; Ahmad, Fauzi; Azhari, Muhamad Azwar (Asian Research Publishing Network (ARPN), 2017)
Increasing requirement in railway vehicle technologies regarding on riding comfort, running safety and speed of railway vehicles are in the increasing trend of studies today. These requirements are opposed by the fact that the condition of the tracks is getting worse and maintenance cost is becoming expensive. In view of this conflict, conventional suspension concepts are not able to overcome all these problems. This paper investigates the performance of semi-active control of lateral suspension system namely fuzzy body-based skyhook and fuzzy bogie-based skyhook for the purpose of attenuating the effects of track irregularities to the body lateral displacement, body roll angle and unwanted yaw responses of railway vehicle. The controller is optimized on 17 degrees of freedom railway vehicle dynamics model and showing better dynamics performance than its counterparts.